Caractérisation physique du fruit et valeur nutritionnelle de la pulpe de karité (Vitellaria paradoxa) collecté dans différents parcs au Bénin. - AHOUANSOU, Roger Houêchéné; KOUGBLENOU, Nadège; AISSI, Vahid; HOUSSOU, Paul; PADONOU, Wilfried; FANDOHAN, Pascal; MENSAH, GUY APOLLINAIRE; SOUMANOU, MANSOUROU MOHAMED (My University, 2012)
In Benin, the Shea fruit pulp undergoes significant post-harvest loss due to its low valorization. A better valorization requires the knowledge of the physical properties of the fruit and the nutritional values of its pulp. The collected fruits in three parklands from a survey of transformer's perception were characterized through their visual observations, the determination of their dimensions and pulp proportions. The nutritional value of pulp was evaluated through its chemical characterization. The results of this study revealed that four forms (forms: ovoid, round, ellipsoid and fusiform) identify the physical aspect of Shea fruits in the Shea parklands. The average length, diameter at the equator, mass and pulp proportion of fruits were 45,30 ± 9,90 mm, 36,30 ± 5,90 mm, 40,4 g and 60% respectively. The physicochemical characterization showed that the Shea fruit pulp contained 5,23% protein, 6,32% fiber, 3,59% ash, 14,08% total sugars, 79,48% moisture and minerals (Ca, K, Mg, P). Except the ash content, no significant variation was observed (p ≥ 5%) between the localities within the parks relatively to the studied physicochemical parameters which however, vary according to the form of the fruits. With a pulp proportion higher than 55% and an interesting proximate composition, the study showed that all forms of Shea fruits found in Benin can be valorized and consumed as a fruit.
Keywords: Vitellaria paradoxa; pulpe; forme du fruit; caractéristiques physico-chimiques; valorisation; perte; post-récolte